Exploring context specific anti-smoking warning labels on cigarette packs: a quasi-experiment - Atiya Abdul Karim; Sumera Inam; Muhammad Tahir Rizwan Khan; kashif Shaffique (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the impact of introducing newly-designed warning labels in relation to the available conventional cigarette packs. Method: The quasi-experimental study was conducted at four co-educational academic institutions selected using cluster random sampling technique in Gulshan-e-Iqbal town of Karachi from September 2016 to October 2017. The respondents, aged 16-24 years, were exposed with an experimental condition using five graphic cards; each comprising of two separate labels; label 1 being a cigarette pack currently rotated, and label 2 being the newly designed graphic and text warning label. Each participant responded over efficacy measures for each label separately. The difference in the efficacy scores between the two labels was assessed using repeated measure ANOVA with Bonferroni correction in analysis. Results: Of the 388 students, 256(66%) were males and 132(34%) were females. The overall mean age was 18±2.76 years. Also, 188(48.5%) subjects were studying in higher secondary, 179(46.1%) undergraduate and 21(5.4%) postgraduate levels. Of them, 104(26.8%) were ever-smokers and 284(73.2%) reported to be never-smokers. In the newly-designed warning label elements of ‘poverty’ and ‘not to start smoking’ in the current cigarette pack were significant (p=0.006). Non-smoking males perceived newly-designed label element ‘dead person’ as fear-arousing (p=0.045), while non-smoking females considered ‘look after family’ as efficacious (p=0.024). Conclusion: There was some evidence of variation in efficacy scores after stratifying on gender and smoking status. A more holistic approach is needed in this regard. Key Words: Cigarette packaging, Cigarette smoking, Health warning labels, Quasi-experiment, Self-efficacy, Tobacco. Continuous...